Solar wind monitor—a school geophysics project. (19th February 2018) - Robinson, Ian
Abstract: Described is an established geophysics project to construct a solar wind monitor based on a nT resolution fluxgate magnetometer. Low-cost and appropriate from school to university level it incorporates elements of astrophysics, geophysics, electronics, programming, computer networking and signal processing. The system monitors the earth's field in real-time uploading data and graphs to a website every few minutes. Modular design encourages construction and testing by teams of students as well as expansion and refinement. The system has been tested running unattended for months at a time. Both the hardware design and software is published as open-source [1, 10].